2022
DOI: 10.1590/fst.25022
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory to analysis the effects of the dirrerent roles of mathca on lipid metabolism and intestinal flora regulation between normal and diabetic mice fed a high-fat diet

Abstract: Fast food is becoming increasing popular as a social phenomenon, and it usually contains high fat contents. Matcha is one versatile tea, and its application in food brings lots of new consumers. Herein, a high-fat diet containing matcha was prepared, and in this study we investigated the effects of such a diet on lipid metabolism and intestinal flora of normal and diabetic mice. Results showed that diabetes had significant weight loss, hyperphagia, hyperlipidemia and intestinal flora disturbance, with particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 45 publications
1
4
0
Order By: Relevance
“…This often melts to form bonded complexes together, resulting in the formation of sizeable agglomerates 59 . Microwave modification of starch granules represents functional components in health‐centric diets with a low glycemic index and also serves as an alternative to dietary fats, while the impact on the protein agglomeration presents a potential utilization of the flour as emulsifier in food formulation 44,60 . Similar observation from studies with microwave‐treated corn and quinoa flour aligns with the present study 32,61 .…”
Section: Resultssupporting
confidence: 86%
“…This often melts to form bonded complexes together, resulting in the formation of sizeable agglomerates 59 . Microwave modification of starch granules represents functional components in health‐centric diets with a low glycemic index and also serves as an alternative to dietary fats, while the impact on the protein agglomeration presents a potential utilization of the flour as emulsifier in food formulation 44,60 . Similar observation from studies with microwave‐treated corn and quinoa flour aligns with the present study 32,61 .…”
Section: Resultssupporting
confidence: 86%
“…As can be seen from Table 5 and Figure 8, within the range of observed actual dose concentration, the action curves of TPs and its main catechin monomer in PYS solution mainly showed a downward opening parabolic shape (quadratic). The results showed that, under the cross-influence of multiple factors, in microecological balance (Liu et al, 2022a;Zhao and Zhang, 2020); and affect and change the internal and external transport efficiency of nutrients, including downregulating the expression of dependent glucose cotransporter 1 (Hossain et al, 2002), protecting islet cells and promoting insulin secretion (Wang et al, 2010), alleviating insulin signal blockade, and promoting sugar oxidation (Bose et al, 2008) and lipid metabolism in vivo (Huang et al, 2013).…”
Section: Analysis Of the Effect Of Phenolic Components On The Hypogly...mentioning
confidence: 99%
“…Diabetes mellitus is a worldwide disease; the number of patients has increased significantly in recent years, and it has become one of the major diseases threatening human health (Li et al, 2020). The results based on studies of modern model animals (Liu et al, 2022a;Liu et al, 2022c;Zhang et al, 2020) and people (Adu et al, 2022;Mortazavi et al, 2018) showed that tea has great potential in promoting the balance of blood glucose.…”
Section: Introductionmentioning
confidence: 99%
“…A high‐fat diet can cause elevated levels of free radicals and lipid metabolism disorders in the body. However, mung bean peptides have been reported to improve high‐fat‐induced disorders and significantly increase levels of liver antioxidant enzymes and indicators, such as total cholesterol and triglycerides (Liu, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Kusumah et al ( 2020 ) researched the antioxidant potential of a mung bean proteolytic solution by measuring its 2,2′‐Azino‐bis‐(3‐ethylbenzothiazoline‐6‐sulfonate) radical scavenging, ferrous ion chelating ability, and oxygen radical absorption capacity. Xie et al ( 2019 ) and Liu ( 2022 ) proved that mung bean protein hydrolysate has a good protective effect on hydrogen peroxide (H 2 O 2 )‐induced NCTC‐1469 cells, and it has a significant promotional effect on hepatic HDL and antioxidant enzyme levels in high‐fat‐induced mice. These results implied that the antioxidant capacity of mung bean protein hydrolysate is associated with the regulation of body metabolism.…”
Section: Introductionmentioning
confidence: 99%